Barack Obama the story - Maraniss, David (Simon & Schuster Paperback, 2012)
Based on hundreds of interviews and documents, this book chronicles the life of Barack Obama and the forces that shaped him, from early childhood through his adult years, as he became the first black president of the United States. In it the author reveals the real story of Obama's beginnings: child of a black man from Luoland in Africa and a white woman born in Texas. He charts the fortunes of the two disparate families, polar opposites in every way, which produced these two extraordinary individuals, who met briefly in Hawaii, never cohabited, and married only to legitimize the child born of that union. At the heart of Obama's psyche and his political beliefs, and therefore his presidency, is his lifelong struggle to understand the extreme duality of his identity.